Histopathological of Mice (Mus musculus) Liver Induced by Lead (Pb) Orally - Kodariah, Liah; Efrida, Pakpahan Suyarta; Aditya, Nugraha; Nurzal, Zalzabila Rena (Universitas Nahdlatul Ulama Surabaya, 2023)
Lead (Pb) is a prominent heavy metal emitted by motor vehicle exhausts, factory and mining fumes. Its presence in the atmoshpere can endure for up to seven days, posing a considerable risk of contaminating surrounding food and beverages. Lead enters the body through inhalation and the skin. Lead can also enter the human body via the oral route and accumulate in the body. It causes health problems such as oxidative stress and damage human organs such as the kidneys and liver. This research aims to examine the effect of oral lead exposure on the liver histopathology of Swiss Webster strain mice (Mus musculus). Employing a non-probability sampling technique, 25 male mice were divided into 5 groups: negative control, K2, K3, K4 and K5. These mice were administered a daily oral dose of 0.5 mL and subsequently euthanized in CO2 chamber the following week for liver dissection. The findings reveal signs of hydropic degeneration characterized by cellular swelling, irregular shapes, and disrupted organelles in groups K2, K3, K4, and K5. In addition, the mean degree of liver damage was observed as 0 for the negative control, 1 for group K2, 1 for group K3, 2 for group K4, and 3 for group K5. In conclsuin, this study confirms that lead exposure can result in dentrimenal liver histopathology changes in mice.